Research note: double digest restriction site associated DNA sequencing is a suitable alternative to high density SNP chips for genomic selection of layers - Mathilde Doublet; Lorry Bécot; Frédéric Lecerf; Sophie Allais (Poultry Science)
For the genomic selection of laying hens, the costs of genotyping are still a challenge. Alternative genotyping approaches as low density SNP chips have been developed by breeding companies to avoid the use of the high-density SNP chip (HD). Another approach called double digest restriction site associated DNA sequencing (ddRAD-seq), associated with an appropriate quality control was also proven to be reliable to genotype laying hens. From this perspective, the use of ddRAD-seq genotypes as an alternative to HD SNP chip genotypes was studied for the genomic evaluation of 179 candidate individuals in a commercial pure line of laying hens of Rhode Island.Genomic evaluations based on ancestry were performed in three different scenari and for four egg quality traits. The first scenario is the reference scenario using only HD SNP chip genotypes. The genomic estimated breeding values (GEBV) were calculated for the 179 candidates with 437 individuals as the reference population (GEBVHDchip437). In the second scenario, the reference population included only the 50 individuals with true ddRAD-seq genotypes and GEBVddRAD-seq50 were calculated for the 179 candidates, based on their ddRAD-seq genotypes. Finally, for the third scenario of genomic evaluation, the reference population was constituted of 437 individuals, with simulated ddRAD-seq genotypes. The GEBVddRAD-seq437 were calculated for the 179 candidates based on their true ddRAD-seq genotypes. Then, Spearman correlations were calculated between GEBVddRAD-seq50 or GEBVddRAD-seq437 and the reference GEBVHDchip437.The mean rank correlation between GEBVHDchip437 and GEBVddRAD-seq50 was 0.92. The mean correlation between GEBVHDchip437 and GEBVddRAD-seq437 was 0.98. The reduced reference population of the GEBVddRAD-seq50 scenario didn't permit for a good representation of the genetic diversity in the population. But, with an equivalent reference population, genomic evaluation based on ddRAD-seq genotypes achieves similar results as genomic evaluation based on HD SNP chip genotypes.